The representation of the approval of the ASD law: a multimodal analysis of the news in Chilean digital newspapers - Cárcamo, Benjamín. (Universidad Nacional Mayor de San Marcos, 2023)
Multimodality continues to gain importance in discourse analysis studies as technology has increased readers’ access to digital content. Considering the impact of the press on the perception of reality, it is important to reveal how different human experiences are represented through the use of a combination of semiotic resources. In this context, the present study aims to analyze the multimodal representation of the approval of the autism spectrum disorder (ASD) law in the four most visited Chilean digital newspapers. For the construction of the methodological framework, the proposals of social actors by van Leeuwen (2003), adapted by Vásquez-Rocca and Manghi (2020); the proposal of visual forms of Visual Grammar (Kress and van Leeuwen, 2007); and notions of Systemic Functional Grammar (Halliday & Matthiessen, 2014) were integrated. Among the findings, deputies were identified as main social actors in three of the four media outlets analyzed. Only in one of the media ASD people and their families are the ones that emerge as protagonists. In addition, while the political figures are represented by means of a naturalistic modality, the ASD community is put in the background by means of an abstract modality. These results indicate that there is a strong trend towards making the ASD community invisible in favor of valuing political figures and particular political parties.
A representação da aprovação da lei do TEA: uma análise multimodal das notícias em chilenos jornais digitais.
La representación de la aprobación de la ley TEA: un análisis multimodal de las noticias en periódicos digitales chilenos
Keywords: Digital newspapers; Multimodality; Autismo; Semiótica